2007
DOI: 10.1093/eurheartj/ehl470
|View full text |Cite
|
Sign up to set email alerts
|

Both vitamin B6 and total homocysteine plasma levels predict long-term atherothrombotic events in healthy subjects

Abstract: tHcy and plasma vitamin B6 are long-term independent risk factors for coronary and cerebrovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Homocysteine metabolism is dependent on the concentrations of B vitamins; that is, folate, serum vi- tamin B12 and vitamin B6 status, which may play some part in the cardiovascular events mediated by hCys plasma concentrations [49]. Low circulating folate and vitamin B12 concentrations lead to high fasting total homocysteine concentrations in humans [50].…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine metabolism is dependent on the concentrations of B vitamins; that is, folate, serum vi- tamin B12 and vitamin B6 status, which may play some part in the cardiovascular events mediated by hCys plasma concentrations [49]. Low circulating folate and vitamin B12 concentrations lead to high fasting total homocysteine concentrations in humans [50].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that Hcy plasma concentration decreased significantly after the CB 6 6 has an important role in the prevention of atherosclerosis regardless of the reduction of plasma homocysteine concentration, but the exact mechanism responsible for this remains unclear [27][28][29] . One plausible Heart function, oxidative stress and vitamin B 6 mechanism is the endogenous production of H2S by the transsulfuration pathway that mediates cysteine production from catabolism of Hcy.…”
Section: Discussionmentioning
confidence: 83%
“…A prospective study of the population from north-eastern Italy confirmed that in long -term follow-up, Hcy and vitamin B 6 are the best prognostic markers of coronary and cerebral events in healthy individuals. 30 It has been shown that supplementation with folic acid not only lowered the Hcy level but also effectively reduced the risk of stroke by 18% in individuals with no history of stroke. 11 The results of a meta-analysis conducted by Lee et al 12 indicated that folic acid supplementation did not have a major effect on averting stroke.…”
Section: Methodsmentioning
confidence: 99%